A development process for the design, implementation and code generation of fault tolerant reconfigurable real time systems. (2016) - Gabsi, Wafa; Zalila, Bechir; Hugues, JÁ¨rÁ´me
The implementation of hard real-time systems is an extremely tedious task today due to safety and dynamic reconfiguration requirements. For that, whatever the taken precautions, the occurrence of faults in such systems is sometimes unavoidable. So, developers have to take into account the presence of faults since the design level. In this context, we notice the need of techniques ensuring the dependability of real-time distributed dynamically reconfigurable systems. We focus on fault-tolerance, that means avoiding service failures in the presence of faults. In this paper, we have defined a development process for modelling and generating fault tolerance code for real-time systems using aspect-oriented programming. First, we integrate fault tolerance elements since the modelling step of a system in order to take advantage of features of analysis, proof and verification possible at this stage using AADL and its annex error model annex. Second, we extend an aspect-oriented language and adapt it to comply with real-time requirements. Finally, we define a code generation process for both functional preoccupations and cross-cutting ones like fault tolerance and we propose an extension of an existent middleware. To validate our contribution, we use AADL and its annexes to design a landing gear system as an embedded distributed one.